2023
DOI: 10.2196/40733
|View full text |Cite
|
Sign up to set email alerts
|

Translating and Adapting the DISCERN Instrument Into a Simplified Chinese Version and Validating Its Reliability: Development and Usability Study

Abstract: Background There is a wide variation in the quality of information available to patients on the treatment of the diseases afflicting them. To help patients find clear and accessible information, many scales have been designed to evaluate the quality of health information, including the Patient Education Materials Assessment Tool; the Suitability Assessment of Materials for evaluation of health-related information for adults; and DISCERN, an instrument for judging the quality of written consumer hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…We found that the model was effective in the translation of the PEMAT-P into the C-PEMAT-P. This finding confirms the findings reported by some recent studies [34][35][36][37], which also attested to the effectiveness of this model in the cross-lingual, cross-cultural translation of health-related instruments and materials. We adopted back-translation to verify the translation equivalence of the C-PEMAT-P by requesting a native English speaker to compare the back-translated English version and the original English version of the PEMAT-P in terms of CL and SI, therefore, minimizing translation errors.…”
Section: Translationsupporting
confidence: 91%
“…We found that the model was effective in the translation of the PEMAT-P into the C-PEMAT-P. This finding confirms the findings reported by some recent studies [34][35][36][37], which also attested to the effectiveness of this model in the cross-lingual, cross-cultural translation of health-related instruments and materials. We adopted back-translation to verify the translation equivalence of the C-PEMAT-P by requesting a native English speaker to compare the back-translated English version and the original English version of the PEMAT-P in terms of CL and SI, therefore, minimizing translation errors.…”
Section: Translationsupporting
confidence: 91%
“…For example, if “ignore” in Item 16 were forward-translated into “hūshì” (the trait of neglecting responsibilities and lacking concern), “mòshì” (willful lack of care and attention, disregard), “bù lǐcǎi” (fail to acknowledge, give little or no attention to), “qīngshì” (treat with contemptuous disregard), “lěngyù” (a refusal to recognize someone you know), “mièshì” (look down on with disdain), or “páichì” (marginalize, relegated to a lower or outer edge, as of specific groups of people), different degrees of discrimination or negative emotions would be induced, which is not intended in the original English scale. These translations would naturally lead to misleading backward translations, making translation equivalence testing ( 54 , 55 ) considerably challenging. Translations thus produced could not effectively explore the cognitive, emotional, and behavioral domains of stigma held by the general public, therefore failing to gain a better understanding of dementia public stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus informed, we focused on panel discussions after literal translation, making full use of the potential advantages of the panel members: the language proficiency of native Chinese speakers (MJ, YS, and WC) and native English speakers (L-FL, SK, AB-W, and SS); the health translation experience of bilingual translators (MJ, YS, and WC); and the expertise of the scale author of the DPSS (SK) and content experts (L-FL, AB-W, and SS) who are engaging in studies on mental health with a special focus on dementia. Such penal discussions ensured not only the linguistic appropriateness and comprehensibility as well as cultural relevance and accessibility of the translated scale but also the maintenance of the original meaning and intent of the source scale ( 54 ). The method developed was presented schematically in the RESULTS section.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Video quality was assessed using the DISCERN tool [ 23 ], which includes 16 items evaluating “reliability” (items 1–8), “treatment choices” information quality (items 9–15), and “overall quality” (item 16). Items 1—15 are coded using a 5-point Likert scale where 1 = “No” (not meeting the criterion), 3 = “Partially” (partly meeting the criterion), and 5 = “Yes” (fully meeting the criterion).…”
Section: Quality Assessmentmentioning
confidence: 99%